Research reviews and prospects of gut microbiota in liver cirrhosis: a bibliometric analysis (2001–2023) - Zhu, Xiaofei; Zhou, Ziyuan; Pan, Xiaxia (Frontiers in Microbiology, 2024)
The gut-liver axis has emerged as a focal point in chronic liver disorders, prompting more research into the role of the gut microbiota in liver cirrhosis. In individuals with liver cirrhosis, changes in the structure and function of the gut microbiota are closely tied to clinical prognosis. However, there is a scarcity of bibliometric evaluations conducted in this particular field. This study is aiming to conduct a complete analysis of the knowledge structure and centers pertaining to gut microbiota in liver cirrhosis using bibliometric methods. Publications on gut microbiota and liver cirrhosis from 2001 to 2023 are sourced from the Web of Science Core Collection. For the bibliometric analysis, we employ VOSviewer, CiteSpace, and the R package "bibliometrix". Our study encompasses a comprehensive collection of 3109 articles originating from 96 countries, with notable contributions from leading nations such as the United States and China. The quantity of publications concerning the gut microbiota of liver cirrhosis rises annually.